2023
DOI: 10.1039/d2tc03536g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled molecules as selective contacts in CsPbBr3 nanocrystal light emitting diodes

Abstract: Metal halide perovskite nanocrystals have demonstrated their potential as light sources when forming part of efficient light emitting diodes (LEDs). However, operational stability and efficiency are compromised primarily because of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The derivative 83 , also known as EADR03, gave PCE of 21.2% and is currently commercialized while the derivative 84 , EADR04, has demonstrated promising results in the increase of the efficiency and lifetime in PeLEDs. 87…”
Section: Carbazole-samsmentioning
confidence: 99%
See 1 more Smart Citation
“…The derivative 83 , also known as EADR03, gave PCE of 21.2% and is currently commercialized while the derivative 84 , EADR04, has demonstrated promising results in the increase of the efficiency and lifetime in PeLEDs. 87…”
Section: Carbazole-samsmentioning
confidence: 99%
“…The derivative 83, also known as EADR03, gave PCE of 21.2% and is currently commercialized while the derivative 84, EADR04, has demonstrated promising results in the increase of the efficiency and lifetime in PeLEDs. 87 Conjugated and aromatic spacer groups exhibit effective hole-transporting capabilities in comparison with the aliphatic linkers, along with higher stability due to the stabilization of the electron-rich carbazole core through electron/charge delocalization. This was also demonstrated with a series of molecules containing the same functional group that MeO-2PACz 65, but with one and two aromatic rings as a spacer group, in addition to the cyanoacetic acid moiety as an anchoring group.…”
Section: Carbazole-samsmentioning
confidence: 99%
“…[1][2][3][4][5] In particular, perovskite CsPbX 3 QDs, where X is the halide anion (generally Cl À for blue emission, Br À for green emission and I À for red emission), have been demonstrated to be excellent candidates as emitters in light-emitting diodes (LEDs); besides, considerable efforts have been devoted to blue and green Pe-QLEDs. [6][7][8][9][10][11][12] However, it is worth noting that the reported research studies mainly focused on the optimization of emitting layers of QDs to achieve higher device performance, while little attention was paid to the design of charge transport layers (CTLs). [13][14][15] According to the basic operating principle of Pe-QLEDs, [16][17][18] the charge carriers that originate from two electrodes and transport through the hole transport layer (HTL) and electron transport layer (ETL) are effectively confined within the active layer of QDs for radiative recombination, and it could be easily found that the device efficiency is strongly affected by the balanced charge transportation in the CTL.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report two new spiro-cored HTMs, i.e., N 2 ,N 2 ,N 20 ,N 20 ,N 7 ,N 7 -hexakis(4-methoxyphenyl)-7 0 -( 4 The outermost OMe moieties could form intermolecular weak hydrogen bonds to realize high solvent resistance of the two HTMs and good thermal stability. As expected, excellent thermal stability, which is a basic requirement for efficient HTMs, was also demonstrated in two spiro-typed compounds with T g values of 162 and 197 1C, respectively.…”
Section: Introductionmentioning
confidence: 99%